Treatment preferences for preventive interventions for rheumatoid arthritis: Protocol of a mixed methods case study for the Innovative Medicines Initiative PREFER project - Falahee, Marie; Simons, Gwenda; Disantostefano, Rachael L.; Valor Méndez, Larissa; Radawski, Christine; Englbrecht, Matthias; Schölin Bywall, Karin; Tcherny-Lessenot, Stephanie; Kihlbom, Ulrik; Hauber, Brett; Veldwijk, Jorien; Raza, Karim (BMJ Open, 2021)
Introduction Amidst growing consensus that stakeholder decision-making during drug development should be informed by an understanding of patient preferences, the Innovative Medicines Initiative project â € Patient Preferences in Benefit-Risk Assessments during the Drug Life Cycle' (PREFER) is developing evidence-based recommendations about how and when patient preferences should be integrated into the drug life cycle. This protocol describes a PREFER clinical case study which compares two preference elicitation methodologies across several populations and provides information about benefit-risk trade-offs by those at risk of rheumatoid arthritis (RA) for preventive interventions. Methods and analysis This mixed methods study will be conducted in three countries (UK, Germany, Romania) to assess preferences of (1) first-degree relatives (FDRs) of patients with RA and (2) members of the public. Focus groups using nominal group techniques (UK) and ranking surveys (Germany and Romania) will identify and rank key treatment attributes. Focus group transcripts will be analysed thematically using the framework method and average rank orders calculated. These results will inform the treatment attributes to be assessed in a survey including a discrete choice experiment (DCE) and a probabilistic threshold technique (PTT). The survey will also include measures of sociodemographic variables, health literacy, numeracy, illness perceptions and beliefs about medicines. The survey will be administered to (1) 400 FDRs of patients with RA (UK); (2) 100 FDRs of patients with RA (Germany); and (3) 1000 members of the public in each of UK, Germany and Romania. Logit-based approaches will be used to analyse the DCE and imputation and interval regression for the PTT. Ethics and dissemination This study has been approved by the London-Hampstead Research Ethics Committee (19/LO/0407) and the Ethics Committee of the Friedrich-Alexander-Universität Erlangen-Nürnberg (92_17 B). The protocol has been approved by the PREFER expert review board. The results will be disseminated widely and will inform the PREFER recommendations.
CRIS-Team Scopus Importer:2021-04-19
Keywords: preventive medicine; public health; rheumatology